Superfluid 3He in the zero temperature limit (Review Article): - Pickett, G. R. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 1997)
In this paper we discuss some (and only a small fraction) of the interesting properties of superfluid 3He at the low temperature limit. We concentrate on the unique behaviour and applications of the very dilute excitation gas at the lowest temperatures. This gas has been used for among other things, the probing of the A-B phase interface, the detection of low energy particle events and in the simulation of the creation of cosmic strings.